Pre-service Mathematics teachers’ conceptions of teaching critical thinking - Yong, Leong Chai (2013)
This research aimed to investigate the pre-service mathematics teachers’ conceptions of teaching critical thinking (CT) giving attention to the concepts, roles and importance, teaching strategies, problems faced and courses in their teacher education related to CT. This qualitative research involved 35 pre-service mathematics teachers who had undergoes 12 weeks of teaching practice. They were purposely selected from the Faculty of Education in a public university located in Johor Bharu. The data were collected using open-ended questions which were analyzed using NVIVO 10.0. The findings showed that all of the pre-service mathematics teachers have not acquired comprehensive conceptions of CT. All of them realized that teachers have responsibility to improve students’ CT. Majority of them reflected that CT helps students in learning mathematics but many among them did not realize the distinctive advantages of the CT in learning mathematics. Not all of them thought that all students can improve their CT. Besides that, most of them reflected the general strategies and strategies essentially related CT, but they were lack of knowledge in assessing CT during problem solving. The most common problems faced by them in incorporating the CT during their teaching practice were students’ understanding and followed by time consuming. Finally, more than one quarters of them mentioned Environmental Chemistry, followed by pedagogy and teaching methods of science and mathematics taught in teacher education as the subjects they learnt that emphasized CT. The results of the study suggested there is a need for teacher education programs to foster the pre-service mathematics teachers’ conceptions of CT.